Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

(HELP ASAP) Use numerals instead of words.

What is the equation of the parabola passing through the points 2,3 , 6,9and 8,0?


HELP ASAP Use Numerals Instead Of WordsWhat Is The Equation Of The Parabola Passing Through The Points 23 69and 80 class=

Sagot :

Answers:

  • -1 in the first box
  • 19/2 or 9.5 in the second box
  • -12 in the third box

=================================================

Work Shown:

We'll use the template y = ax^2 + bx + c

  • If (x,y) = (2,3) is on the parabola, then y = ax^2+bx+c turns into 3 = a(2)^2 + b(2) + c. That simplifies to 4a+2b+c = 3
  • If (x,y) = (6,9) is on the parabola, then y = ax^2+bx+c turns into 9 = a(6)^2 + b(6) + c. That simplifies to 36a+6b+c = 9
  • If (x,y) = (8,0) is on the parabola, then y = ax^2+bx+c turns into 0 = a(8)^2 + b(8) + c. That simplifies to 64a+8b+c = 0

The system of equations is

[tex]\begin{cases}4a+2b+c = 3\\36a+6b+c = 9\\64a+8b+c = 0\end{cases}[/tex]

We have 3 equations and 3 unknowns.

-----------------------------------

Let's solve the first equation for c

4a+2b+c = 3

2b+c = 3-4a

c = 3-4a-2b

c = -4a-2b+3

Plug that into the second equation and simplify

36a+6b+c = 9

36a+6b+(-4a-2b+3) = 9

32a+4b+3 = 9

32a+4b = 9-3

32a+4b = 6

2(16a+2b) = 6

16a+2b = 6/2

16a+2b = 3 .... we'll use this later

Plug that value of c into the third equation as well

64a+8b+c = 0

64a+8b+(-4a-2b+3) = 0

60a+6b+3 = 0

3(20a+2b+1) = 0

20a+2b+1 = 0

20a+2b = -1

--------------------------

We have a new system of equations. This time it deals with 2 variables instead of 3. We can think of this as a reduced equivalent system.

[tex]\begin{cases}16a+2b = 3\\20a+2b = -1\end{cases}[/tex]

Note how subtracting the terms straight down has the b terms canceling (since 2b-2b = 0b = 0)

The 'a' terms subtract to 16a-20a = -4a

The terms on the right hand side subtract to 3-(-1) = 3+1 = 4

We end up with the equation -4a = 4 which solves to a = -1

Use this value of 'a' to find b

16a+2b = 3

16(-1)+2b = 3

-16+2b = 3

2b = 3+16

2b = 19

b = 19/2

b = 9.5

Now use the values of a and b to find c

4a+2b+c = 3

4(-1)+2(9.5)+c = 3

-4+19+c = 3

15+c = 3

c = 3-15

c = -12

--------------------------

Summary:

The values of a,b,c we found were

  • a = -1
  • b = 19/2 = 9.5
  • c = -12

So the function is

f(x) = -x^2 + (19/2)x - 12

which is equivalent to

f(x) = -x^2 + 9.5x - 12

To check this answer, plug in x = 2, x = 6, x = 8 one at a time. You should get y = 3, y = 9 and y = 0 in that order.

Answer:

f(x)=-x^2+9.5-12

Step-by-step explanation:

- for the first box

9.5 for the second box

-12 for the third box

We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.